Localization of Advanced and Emerging Technologies and How - Ahmadpour, Shahram; ParvizAhadi; Farhang, Yousef (International Journal of Psychosocial Rehabilitation, 2021)
Today, in every organization, the use of advanced and emerging technologies is discussed and the usefulness or necessity of using these technologies is discussed everywhere. The arrival of any new phenomenon in the country, if accompanied by relevant knowledge and the provision of the necessary domestic context, has been properly developed. Localization of defense equipment and technologies is an important issue, and if today Islamic Iran is impenetrable in the field of defense equipment and takes the lead in the world, it is because it is indigenous. Therefore, creating an atmosphere of abuse and incitement of the people in order to prevent the localization and indigenous knowledge of Iran is on the agenda of the enemy. In this article, we examine the localization of advanced and emerging technologies and how.